2018
DOI: 10.1101/342485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling tRNA promoter and processing activities enables specific Pol-II Cas9 guide RNA expression

Abstract: Spatial/temporal control of Cas9 guide RNA expression could considerably expand the utility of CRISPR-based technologies. Current approaches based on tRNA processing offer a promising strategy but suffer from high background. Here we developed a variant screening platform to identify differential sequence determinants of human tRNA promoter and processing activities. Rational design based on the ensuing principles allowed us to engineer an improved tRNA scaffold that enabled highly specific guide RNA productio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…These results are consistent with those reported by Knapp et al (Knapp et al, 2019) showing that tRNAs can generate functional gRNAs that are constitutively and promoter-independently expressed. Knapp et al (2019) designed a tRNA Pro scaffold (Δ, ΔC55A, and ΔC55G) with minimized promoter strength without affecting the processing activity of the tRNA. An interesting addition to our work would be to implement the usage of these tailored tRNAs.…”
Section: B Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those reported by Knapp et al (Knapp et al, 2019) showing that tRNAs can generate functional gRNAs that are constitutively and promoter-independently expressed. Knapp et al (2019) designed a tRNA Pro scaffold (Δ, ΔC55A, and ΔC55G) with minimized promoter strength without affecting the processing activity of the tRNA. An interesting addition to our work would be to implement the usage of these tailored tRNAs.…”
Section: B Discussionsupporting
confidence: 93%
“…However, this extra regulation did not lead to efficient control over the activation of the reporter gene. These results are consistent with those reported by Knapp et al (Knapp et al, 2019) showing that tRNAs can generate functional gRNAs that are constitutively and promoter-independently expressed. Knapp et al (2019) designed a tRNA Pro scaffold (Δ, ΔC55A, and ΔC55G) with minimized promoter strength without affecting the processing activity of the tRNA.…”
Section: B Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S6), the efficiency of multi-gene editing using the PTG strategy was lower than that achieved with the co-injection strategy, likely due to the requirement for simultaneous processing of 4 sgRNAs from a single template. Studies in plants and flies have reported that insertion of a tRNA between the PolIII promoter and the first sgRNA increased transcription efficiency (31), which was found to be due to the additive effect by the innate tRNA's promoter activity (32). We attempted this approach without success (data not shown), an indication of species-specific differences in short RNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…Pol II promoters naturally transcribe mRNAs while pol III promoters naturally transcribe transfer RNAs and small ribosomal RNAs [168]. Pol II promoters are used for temporal and spatial gene expression while pol III promoters for constitutive gene expression [169]. Types of commonly used pol II promoters include CMV and CAG (which uses CMV as an enhancer) [111] and commonly used pol III promoters include U6, 7SK, and H1 [170].…”
Section: Regulatory Elementsmentioning
confidence: 99%